2020
DOI: 10.3389/fphar.2020.01290
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Specialized Pro-Resolving Mediators in Cystic Fibrosis Airways Disease

Abstract: Cystic Fibrosis (CF) is a recessive genetic disease due to mutations of the Cystic Fibrosis Transmembrane Conductance Regulator ( CFTR ) gene encoding the CFTR chloride channel. The ion transport abnormalities related to CFTR mutation generate a dehydrated airway surface liquid (ASL) layer, which is responsible for an altered mucociliary clearance, favors infections and persistent inflammation that lead to progressive lung destruction and respiratory failure. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 382 publications
(510 reference statements)
0
8
0
Order By: Relevance
“…An important aspect of the study was the assessment of biomarkers of inflammation in sputum and peripheral blood samples. It has been shown that RvD1 levels in CF airways could be a contributing factor to chronic airway inflammation, and that CF patients have a reduced capacity to biosynthesize specialized pro-resolving lipid mediators (SPMs), which contributes to the development and duration of the unwanted inflammation [35,36]. SPMs are multipotent regulators of inflammation and resolution, acting on multiple molecular and cell targets to limit inflammation and return to homeostasis, with emerging results encouraging SPMs as candidate drugs for treating infection and chronic inflammation in CF patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of the study was the assessment of biomarkers of inflammation in sputum and peripheral blood samples. It has been shown that RvD1 levels in CF airways could be a contributing factor to chronic airway inflammation, and that CF patients have a reduced capacity to biosynthesize specialized pro-resolving lipid mediators (SPMs), which contributes to the development and duration of the unwanted inflammation [35,36]. SPMs are multipotent regulators of inflammation and resolution, acting on multiple molecular and cell targets to limit inflammation and return to homeostasis, with emerging results encouraging SPMs as candidate drugs for treating infection and chronic inflammation in CF patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…An important feature of CF airway pathogenesis is the excessive and inefficient inflammatory process that could be explained by an altered resolution of inflammation ( Roesch et al, 2018 ; Briottet et al, 2020 ). The finding that resolution of inflammation differs between Cftr tm1Hgu and WT mice is consistent with this aspect of the clinical description of the CF airway disease.…”
Section: Effects Of Air Pollution Exposure In Experimental Models Of ...mentioning
confidence: 99%
“…SPM also have a therapeutic potential in reversing or preventing pollution-induced inflammation ( Kilburg-Basnyat et al, 2018 ; Lu et al, 2018 ; Thatcher et al, 2019 ). Finally, in the airway of CF patients, the biosynthesis of LXA4 and Resolvin D1 (RvD1) SPM are reduced ( Karp et al, 2004 ; Ringholz et al, 2014 ; Eickmeier et al, 2017 ; Briottet et al, 2020 ; Isopi et al, 2020 ) and related to the sustained levels of pro-inflammatory cytokines and bacterial infection, the altered airway surface hydration and pulmonary function ( Verrière et al, 2012 ; Eickmeier et al, 2017 ; Codagnone et al, 2018 ; Ringholz et al, 2018 ; Isopi et al, 2020 ). Taken together, these data highlight a possible particular pulmonary susceptibility of CF patients exposed to particulate air pollution; under these conditions, insufficient inflammation resolution could favor the onset of a chronic inflammatory condition and accelerated progression of the CF airway disease.…”
Section: Effects Of Air Pollution Exposure In Experimental Models Of ...mentioning
confidence: 99%
“…The inflammatory process in CF is complicated 43 , characterised by early and sustained neutrophil influx and high levels of elastase which correlate with structural damage on imaging even in early life. There is some evidence that normal resolution mechanisms are impaired 44 , so that inflammation can persist even if an infective insult is cleared 45 . There is certainly evidence that inflammation persists when CFTR function is corrected 46 .…”
Section: Introductionmentioning
confidence: 99%